Curriculum Management of Local Content in Shaping Religious Behavior - Supriyanto, Heri; Darim, Abu; Ismawati, Ismawati; Taufiq, Ahmad (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2023)
This research employs a qualitative method, focusing on how researchers examine the source of the object by generating narrative data based on observations through a case study approach. The research subjects include the Head of the Madrasah (KM), Deputy Head of the Madrasah (WKM), Local Charge Teacher (GML), and students. Data collection was carried out through interviews, observation, and documentation methods. Data analysis utilized the Milles & Huberman analysis method, involving qualitative descriptive data with an interactive model. This includes data reduction of newly acquired complete data, grouping the data, presenting information after collection, and drawing conclusions from these models. The researchers derived conclusions from the grouped data based on existing sources. The study's findings are as follows: 1) The planning of the local content curriculum in shaping religious behavior involves the Madrasah, guided by the RKT and RKAM, which determine local content programs, subjects, teaching staff, and funding and learning resources. 2) The implementation of the local content curriculum in shaping religious behavior entails reviewing the syllabus, creating lesson plans, and conducting assessments. 3) The outcomes of the local content curriculum in shaping religious behavior encompass local content programs and the evaluation results of local content learning.